Analisis Penerapan Cash Management System Dalam Pengelolaan Keuangan Daerah Di Pik Pulogadung - Sari, Imelda (www.bsi.ac.id, 2020)
Technological innovations are able to quickly make changes in the financial sector in the form of internet-based financial digitalization. This is marked by changes in banking services, from the initial form of cash transactions to non-cash transactions, in their implementation called the Cash Management System (CMS). The implementation of the CMS has brought changes in the Pulogadung Small Industry Village (PIK Pulogadung), marked by the speed of service and time savings for Micro, Small and Medium Enterprises when paying retribution, partners in the procurement of goods and services and for employees of Non Civil Servants Regional Management Units when receive a monthly salary. SWOT analysis can be material to make strategic planning in achieving short-term goals for the Regional Management Unit office and more systematic long-term for the banking industry. Strengthening CMS supporting infrastructure, conducting financial socialization and continuous supervision will be able to improve the implementation of CMS in PIK Pulogadung. The increase in CMS will affect people's lifestyles which will ultimately be able to increase national financial inclusion.